The missing museums: accreditation, surveys, and an alternative account of the UK museum sector. Issue 1 (1st January 2020) - Candlin, Fiona; Larkin, Jamie; Ballatore, Andrea; Poulovassilis, Alexandra
ABSTRACT: Surveys of the UK museum sector all have subtly different remits and so represent the sector in a variety of ways. Since the 1980s, surveys have almost invariably focused on accredited institutions, thereby omitting half of the museums in the UK. In this article we examine how data collection became tied to the accreditation scheme and its effects on how the museum sector is represented as a professionalised sphere. While is important to understand the role of surveys in constructing the museum sector, this article also demonstrates how the inclusion of unaccredited museums drastically changes the profile of the museum sector. We outline the inclusive research methodology of the Mapping Museums project team and compare our findings with those produced when a survey is limited to accredited museums. In so doing, we sketch out an alternative, heterogeneous version of the UK museum sector and make recommendations based on that evidence.